Body mass, marital status, and number of children in the family - I. V. Dovgalev; B. A. Trotsenko; I. V. Tsimbalyuk; V. V. Obraztsov; V. V. Seryakova; A. K. Zapodovnikov; R. S. Karpov (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study the effects of social factors (marital status, the number of children born and raised in the family) on the incidence of body weight (BW) increase. Material and methods. The 15-year follow-up focussed on BW dynamics in men and women, in regard to the changes in their martial status. At baseline, all participants were married (n=845; 327 men and 518 women). To evaluate the effects of the children’s number on increased BW incidence, 238 women aged 40—59 years and having at least one child before the baseline, were examined (≥ 2 children in 163 women, 1 child in 75 women). Increased BW was registered if body mass index (BMI) was 25 kg/m2 or higher. Results. In widowed participants, the incidence of BW increase was lower (1,9 %) than in those married (10,5 %; p<0,01) or divorced (21,4 %; p<0,01). In widowed women, the normalisation of initially increased BW was registered more often (13,5 %), compared to their still married peers (4,3 %; p<0,05). In those still married, BMI increased from 26,95±0,09 to 27,91±0,09 kg/m2 (p<0,001), while in those widowed, it decreased from 29,92±0,24 to 29,34±0,24 kg/m2 (p<0,05). In women with 2 or more children, the incidence of BW increase was higher (85,3 %) than in women with only one child (73,3 %; p<0,05). Conclusion. The change in marital status could affect BW dynamics. Spouse death is an important cause of BW reduction. In women with 2 or more children, increased BW was more common than in women with only one child.